Subdural empyema secondary to contralateral sinusitis: hematogenous dissemination? - Emerson Kennedy Ribeiro de Andrade Filho; José Eduardo Nóbrega Moura; Heitor Dutra de Medeiros; Francisco de Assis Fernandes Tavares; Rivus Ferreira Arruda (Archives of Pediatric Neurosurgery, 2023)
Sinusitis refers to inflammation in the sinuses. Complications of sinusitis are rare and most often affect the orbit. However, in rare cases, these complications may be intracranial. One of these intracranial complications is subdural empyema, which is a loculated suppuration between the dura mater and the arachnoid. Despite its rarity, it has a high mortality rate and is often underestimated by physicians.